Practical Management Science / Second Edition - Albright S. Christian; Broadie Mark; Winston Wayne L (Duxbury - Thomson Learning, 2001)
This book teaches modelling skills through the use of real world examples drawn from finance, marketing, and operations management. Introduction to Modeling, Introductory Spreadsheet Modeling, Introduction to Optimization Modeling, Linear Programming Models, Network Models, Linear Optimization Models with Integer Variables, Nonlinear Optimization Models, Evolutionary Solver: An Alternative Optimization Procedure, Multi-Objective Decision Making, Decision Making Under Uncertainty, Introduction to Simulation Modeling, Simulation Models, Inventory Models, Queueing Models, Regression Analysis, Time Series Analysis and Forecasting, References, Index.